Estimating Phytoplankton Abundance Using Sentinel 2A Images In Langa-Jampue Water Area, Pinrang Regency - Muhtar, Siti Asmutianti; Amran, Muhammad Anshar; Hatta, Muh. (Sam Ratulangi University, 2023)
This study aims to estimate the abundance of phytoplankton using Sentinel-2 imagery in the Langa – Jampue water area of Pinrang Regency for Sentinel-2 image recording on February 28, 2022. This study was conducted from January – July 2022 by taking phytoplankton samples, conducting sample analysis in the laboratory, and processing Sentinel-2 image data on February 28, 2022 recording. The results of the study found 5 classes of phytoplankton, namely Bacillariophyceae, Cyanophyceae, Dyanophyceae, Peridinae, and Dinophyceae with a total of 34 phytoplankton genera and 4 dominating genera, namely Astereonolepsis, Rhizosolenia, Chaetoceros, and Ceratium. The highest phytoplankton abundance was obtained in transect 2 on point with an abundance of 977 cells/liter and the lowest abundance in transect 3 on point 24 which was 282 cells/liter. The regression test results between phytoplankton abundance and pixel band values 8, band 3, and band 2 on Sentinel-2 images produced an r-square value of 0.495 and obtained a positive correlation value between the pixel band 8 value and the phytoplankton abundance value with a correlation value of 0.529 which means that band 8 can be used for estimating phytoplankton abundance in marine remote sensing systems. The result of the paired t-test revealed that the abundance of phytoplankton based on the results of image processing and relative laboratory analysis was equal to a significant value of 0.999 Keywords: Phytoplankton, Sentinel-2 Imagery, Band 8 Abstrak Penelitian ini bertujuan untuk mengestimasi kelimpahan fitoplankton menggunakan citra Sentinel-2 di wilayah perairan Langa – Jampue Kabupaten Pinrang untuk perekaman citra Sentinel-2 pada tanggal 28 Februari 2022. Penelitian ini dilakukan pada bulan Januari – Juli 2022 dengan mengambil sampel fitoplankton, melakukan analisis sampel di laboratorium dan mengolah data citra Sentinel-2 pada perekaman 28 Februari 2022. Hasil dari penelitian ditemukan 5 kelas fitoplankton yaitu Bacillariophyceae, Cyanophyceae, Dyanophyceae, Peridinae, Dinophyceae dengan total 34 genus fitoplankton dengan 4 genus yang mendominasi yaitu Astereonolepsis, Rhizosolenia, Chaetoceros dan Ceratium. Kelimpahan fitoplankton tertinggi didapatkan pada transek 2 yaitu pada titik 9 dengan kelimpahan 977 sel/liter dan kelimpahan terendah pada transek 3 yaitu pada titik 24 dengan kelimpahan 282 sel/liter. Hasil uji regresi antara kelimpahan fitoplankton dan nilai pixel band 8, band 3 dan band 2 pada citra Sentinel-2 menghasilkan nilai r-square yaitu 0,495 dan didapatkan nilai korelasi yang positif antara nilai pixel band 8 dan nilai kelimpahan fitoplankton dengan nilai korelasi 0,529 yang berarti band 8 dapat digunakan untuk pendugaan kelimpahan fitoplankton pada sistem penginderaan jauh kelautan. Dari hasil uji-t paired dapat diketahui bahwa kelimpahan fitoplankton dari hasil pengolahan citra dan hasil analisis laboratorium realtif sama dengan nilai signifikan 0,999 Kata kunci: Fitoplankton, Citra Sentinel-2, Band 8